2019
DOI: 10.1021/acs.orglett.9b00548
|View full text |Cite
|
Sign up to set email alerts
|

N-Chloroformylimidazolidinone Enolates as 1,3-Dipolar Reagents for the Stereoselective Synthesis of 3,4-Dihydroisoquinolones

Abstract: N-Chloroformyl imidazolidinone derivatives of enantiopure amino acids may be deprotonated to give remarkably well-behaved enolates with both nucleophilic and electrophilic character. The enolates undergo diastereoselective C-alkylation with benzylic halides. A Bischler-Napieralski-like cyclization reaction onto the chloroformyl group, induced by either nucleophilic (KI, 2,6-lutidine) or Lewis acid (AlCl3) catalysis, gives substituted 3,4-dihydroisoquinolone derivatives in enantioenriched form. The reaction seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…1a) that was formed cleanly by hydrogenolysis of 5 in THF. These conditions preserved the (surprisingly stable 15,16 ) carbamoyl chloride group. 17 We found that heating 6 to 60 C for 72 h in the presence of Et 3 N and KI induced dearomatizing spirocyclisation to the dienone 7, a compound with clear structural homology to arogenate 1, in 82% yield.…”
Section: Resultsmentioning
confidence: 90%
“…1a) that was formed cleanly by hydrogenolysis of 5 in THF. These conditions preserved the (surprisingly stable 15,16 ) carbamoyl chloride group. 17 We found that heating 6 to 60 C for 72 h in the presence of Et 3 N and KI induced dearomatizing spirocyclisation to the dienone 7, a compound with clear structural homology to arogenate 1, in 82% yield.…”
Section: Resultsmentioning
confidence: 90%
“…Since our original publication, 6 we have optimised the method for diastereoselective formation of trans N -chloroformylimidazolidinones. 7 In this way, 40 g of 2 (R = H) were readily prepared as a single diastereoisomer (our previously reported method gave a mixture of 2 and its cis isomer). Sequential addition of KHMDS to a solution of 2 and 4-bromo- N -methylaniline (the formal equivalent of the aryl electrophile) effected one-pot tandem urea formation and diastereoselective N to C migration of the aryl ring to install the quaternary centre.…”
Section: Resultsmentioning
confidence: 99%
“…Line shape modelling (Figure 1h) gave a correspondingly higher barrier to conversion of the major to the minor rotamer of 71.7 kJ mol -1 at 300 K. The remarkable stability of the carbamoyl chlorides 2 permitted them to be very readily isolated and purified by chromatography on silica, and suggested that despite their electrophilic reactivity it might nonetheless be possible to deprotonate them to form an enolate. 18 In initial investigations, 2a was treated with base at room temperature and quenched with allyl bromide, but only decomposition was noted with LDA, KHMDS or LiHMDS (Table 2, entries 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently described several reactions in which the N -chloroformyl derivative of an imidazolidinone plays a pivotal role, and this work showed that the two diastereoisomers of these carbamoyl chlorides displayed very different reactivities. In one particular family of Bischler–Napieralski-like cyclizations, only the trans isomer was of use.…”
Section: Introductionmentioning
confidence: 99%